Estudio comparativo de síndrome metabólico en pacientes con enfermedad renal crónica estadío 1 a 4 en relación a pacientes bajo terapia de sustitución renal tipo hemodiálisis que asisten al hospital Carlos Andrade Marín de Quito, durante el periodo marzo 2012-agosto 2013. - Abarca Pineda, Magaly Rocío. (2015)
This research was conducted at the Hospital Carlos Andrade Marín in Nephrology in the period March 2012 - August 2013, in order to compare the appearance of the metabolic syndrome in both patients with CKD in conservative management and those subject to hemodialysis. Prospective, comparative descriptive cross in which the two groups was investigated - To meet the objectives a retrospective study. It was found that in patients with CKD stage 1 - 4, 80, 82% have metabolic syndrome, waist circumference predominantly present in 96.97%, HDL Cholesterol diminution in 62.63%, 43.43% the increased value of triglycerides. Moreover CKD patients on hemodialysis Metabolic Syndrome comes in a 75.60%, 88.19% a predominantly by waist circumference, 77.17% for elevated triglycerides, decreased by 64.57% HDL Cholesterol. Therefore we think it advisable to perform better control of patients with greater frequency